A preparation method and application of ZnO-based perovskite solar cell

By using ZnO-based inorganic perovskite materials and specific preparation methods, the problems of poor thermal stability and long-term stability of existing perovskite solar cells are solved, and efficient, stable and repeatable perovskite solar cell devices are achieved.

CN119767933APending Publication Date: 2025-04-04JINGDEZHEN ART VOCATIONAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411855336.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The light absorbing layers of existing perovskite solar cells are mostly organic and inorganic hybrid materials, resulting in poor thermal stability and long-term stability.

Method used

Using ZnO-based inorganic perovskite material, a specific preparation method includes pretreatment substrate, evaporated electron transport layer, spin-coated perovskite layer and hole transport layer, and evaporated gold electrode to form an efficient and stable perovskite solar cell.

Benefits of technology

The crystallization quality of perovskite films is improved, efficient, stable and repeatable inorganic perovskite solar cell devices are achieved, photoelectric conversion is improved, and large-scale production is facilitated.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of battery processing technology, and discloses a ZnO-based perovskite solar cell, comprising a substrate, an electron transport layer, a perovskite layer, a hole transport layer, and an electrode; wherein the substrate comprises one of soda-lime glass, stainless steel foil, titanium foil, PET, and FTO conductive glass; the electron transport layer is made of C60 material, and the perovskite layer is an inorganic perovskite powder in an amount of 0.8 to 1.2 mmol. The preparation method and application of the ZnO-based perovskite solar cell can solve the problems of stoichiometric ratio deviation and introduction of non-perovskite impurities through perovskite powder, improve the crystallization quality of the perovskite film, thereby realizing an efficient, stable and repeatable inorganic perovskite solar cell device, and at the same time, it is made by spin coating, which is convenient for large-scale production, and ensures the uniformity of the hole transport layer and the perovskite layer, and the electron transport layer is made by evaporation, so that the photoelectric conversion rate of the ZnO-based perovskite solar cell is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery processing, and in particular to a preparation method and application of a ZnO-based perovskite solar cell. Background Art

[0002] Perovskite solar cells are a new type of solar cells. The organic-metal halide light-absorbing materials with perovskite structure have excellent light absorption, photoelectric conversion characteristics and excellent photogenerated carrier transport characteristics. Therefore, the perovskite solar cells using this photoelectric conversion material show particularly excellent photoelectric conversion efficiency.

[0003] Perovskite solar cells are generally composed of transparent conductive glass, electron transport layer, perovskite light-absorbing layer, hole transport layer, and metal counter electrode. The light-absorbing layers used in the current high-efficiency batteries in the laboratory are mostly organic-inorganic hybrid perovskite materials, such as MAPbI3 and FAPbI3. Due to the presence of organic components, the thermal stability and long-term stability of the battery are poor. The all-inorganic perovskite materials that replace organic cations with inorganic components have better thermal stability and relatively better application prospects. Therefore, improving the battery preparation process and enhancing the performance of inorganic perovskite batteries is currently an important task. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing and applying a ZnO-based perovskite solar cell, which solves the problem that the light-absorbing layers of the cells with higher efficiency in the laboratory are mostly organic-inorganic hybrid perovskite materials, such as MAPbI3 and FAPbI3, etc., and the thermal stability and long-term stability of the cells are poor due to the presence of organic components.

[0006] (II) Technical solution

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A ZnO-based perovskite solar cell comprises a substrate, an electron transport layer, a perovskite layer, a hole transport layer, and an electrode;

[0009] The substrate includes one of soda-lime glass, stainless steel foil, titanium foil, PET, and FTO conductive glass;

[0010] The electron transport layer is made of C60 material, and the perovskite layer is made of inorganic perovskite powder with an amount of 0.8 to 1.2 mmol;

[0011] The hole transport layer is Spiro-OMeTAD 50-72 mg, and the electrode is a vapor-deposited Au electrode.

[0012] A method for preparing a ZnO-based perovskite solar cell comprises the following steps:

[0013] Step 1, selecting a substrate and pre-treating the substrate;

[0014] The pretreatment method is to first rinse the substrate with deionized water, use a cleaning agent to assist in cleaning during this process, place the substrate in an ultrasonic cleaning machine after cleaning, and then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence. After the ultrasonic cleaning is completed, the substrate is transferred to a dust-free shed to remove residual liquid on the surface;

[0015] Step 2, preparing an electron transport layer on the pretreated substrate;

[0016] The substrate obtained after pretreatment was transferred to a rotary evaporator and evaporated 30 nm thick C60 as an electron transport layer;

[0017] Step 3, preparing a perovskite layer based on step 2;

[0018] Dissolving 0.8-1.2 mmol of inorganic perovskite powder in a mixed solvent of 0.1-0.2 mL of dimethylformamide (DMF) and 0.8-1.0 mL of dimethyl sulfoxide (DMSO) to obtain a perovskite precursor solution;

[0019] Then, the perovskite precursor solution is spin-coated on the surface of the electron transport layer obtained in step 2, the spin-coating speed is 3000-5000 rpm, the spin-coating time is 40-60 seconds, and 0.1-0.6 mL of ethyl acetate is added to the rotating surface as an anti-solvent before the spin-coating is completed, and finally, pre-crystallization is performed at 45-55° C., and then annealing is performed at 160-200° C. to obtain a perovskite photoactive layer with a thickness of 250-350 nm;

[0020] Step 4: prepare a hole transport layer based on step 3; dissolve 50-72 mg Spiro-OMeTAD in 0.8-1 mL chlorobenzene solution, mix well to obtain a Spiro-OMeTAD spin coating solution, and deposit 80 μL Spiro-OMeTAD spin coating solution on the surface obtained in step 3;

[0021] Step 5, preparing an electrode on the surface of the substrate obtained in step 4 to complete the preparation of the perovskite solar cell;

[0022] The electrode is prepared by evaporating a 50-80 nm thick Au electrode on the surface of the Spiro-OMeTAD hole transport layer obtained in step 4 under a vacuum degree of 3×10-4 to 6×10-4 Pa.

[0023] Preferably, the cleaning time in step 1 is greater than 10 minutes, and the ultrasonic cleaning time is 30 minutes.

[0024] Preferably, the residual liquid is removed in step 1 by blowing away the residual liquid on the surface of the substrate with high-pressure pure nitrogen gas.

[0025] Preferably, the evaporation time in step 2 is 10-30 minutes.

[0026] Preferably, the pre-crystallization time in step three is 1-2 minutes, and the annealing time is 8-12 minutes.

[0027] Preferably, the spin coating speed in step 4 is 4000 rpm, and the spin coating time is 30 s.

[0028] An application of a ZnO-based perovskite solar cell. The ZnO-based perovskite solar cell of the present invention can be applied to photovoltaic solar cells, or to solar street lamps and other equipment that can be used for photovoltaic power generation.

[0029] (III) Beneficial effects

[0030] Compared with the prior art, the present invention provides a method for preparing a ZnO-based perovskite solar cell and its application, which has the following beneficial effects:

[0031] 1. The preparation method and application of the ZnO-based perovskite solar cell. The ZnO-based perovskite solar cell manufactured by the above steps, the perovskite powder can solve the problems of stoichiometric ratio deviation and introduction of non-perovskite impurities, improve the crystallization quality of the perovskite film, thereby realizing efficient, stable and repeatable inorganic perovskite solar cell devices. At the same time, it is manufactured by spin coating, which is convenient for large-scale production and ensures the uniformity of the hole transport layer and the perovskite layer. The electron transport layer is manufactured by evaporation, so that the photoelectric conversion rate of the ZnO-based perovskite solar cell is higher. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] A ZnO-based perovskite solar cell comprises a substrate, an electron transport layer, a perovskite layer, a hole transport layer, and an electrode;

[0034] The substrate includes one of soda-lime glass, stainless steel foil, titanium foil, PET, and FTO conductive glass;

[0035] The electron transport layer is made of C60 material, the perovskite layer is an inorganic perovskite powder with an amount of 0.8-1.2 mmol; the hole transport layer is Spiro-OMeTAD with an amount of 50-72 mg, and the electrode is a vapor-deposited Au electrode. Example 1:

[0036] A method for preparing a ZnO-based perovskite solar cell comprises the following steps:

[0037] Step 1, selecting a substrate and pre-treating the substrate;

[0038] The pretreatment method is to first rinse the substrate with deionized water, use a cleaning agent to assist in cleaning during this process, place the substrate in an ultrasonic cleaning machine after cleaning, and then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence. After the ultrasonic cleaning is completed, the substrate is transferred to a dust-free shed to remove residual liquid on the surface;

[0039] Among them, the cleaning time is 30 minutes, and the ultrasonic cleaning time is 30 minutes;

[0040] The residual liquid is removed by blowing away the residual liquid on the surface of the substrate with high-pressure pure nitrogen gas;

[0041] Step 2, preparing an electron transport layer on the pretreated substrate;

[0042] The substrate obtained after pretreatment was transferred to a rotary evaporator and evaporated 30 nm thick C60 as an electron transport layer;

[0043] Among them, the evaporation time is 30min;

[0044] Step 3, preparing a perovskite layer based on step 2;

[0045] 1.2 mmol of inorganic perovskite powder was dissolved in a mixed solvent of 0.2 mL of dimethylformamide (DMF) and 1.0 mL of dimethyl sulfoxide (DMSO) to obtain a perovskite precursor solution;

[0046] Then, the perovskite precursor solution was spin-coated on the surface of the electron transport layer obtained in step 2, the spin-coating speed was 5000 rpm, the spin-coating time was 60 seconds, and 0.6 mL of ethyl acetate was added to the rotating surface as an anti-solvent before the spin-coating was completed; finally, pre-crystallization was performed at 45° C. for 2 minutes, and then annealing was performed at 200° C. for 12 minutes to obtain a perovskite photoactive layer with a thickness of 250 to 350 nm;

[0047] Step 4: prepare a hole transport layer based on step 3; dissolve 72 mg of Spiro-OMeTAD in 1 mL of chlorobenzene solution, mix well to obtain a Spiro-OMeTAD spin coating solution, take 80 μL of Spiro-OMeTAD spin coating solution and deposit it on the surface obtained in step 3, the spin coating speed is 4000 rpm, and the spin coating time is 30 s;

[0048] Step 5, preparing an electrode on the surface of the substrate obtained in step 4 to complete the preparation of the perovskite solar cell;

[0049] The electrode is prepared by evaporating a 50-80 nm thick Au electrode on the surface of the Spiro-OMeTAD hole transport layer obtained in step 4 under a vacuum degree of 3×10-4 to 6×10-4 Pa.

[0050] The ZnO-based perovskite solar cell of the present invention can be applied to photovoltaic solar cells, or to solar street lamps and other devices that can be used for photovoltaic power generation.

[0051] The ZnO-based perovskite solar cell produced by the above steps, the perovskite powder can solve the problems of stoichiometric ratio deviation and the introduction of non-perovskite impurities, improve the crystallization quality of the perovskite film, thereby realizing efficient, stable and repeatable inorganic perovskite solar cell devices. At the same time, it is produced by spin coating, which is convenient for large-scale production and ensures the uniformity of the hole transport layer and the perovskite layer. The electron transport layer is produced by evaporation, so that the photoelectric conversion rate of the ZnO-based perovskite solar cell is higher.

[0052] Embodiment 2:

[0053] A method for preparing a ZnO-based perovskite solar cell comprises the following steps:

[0054] Step 1, selecting a substrate and pre-treating the substrate;

[0055] The pretreatment method is to first rinse the substrate with deionized water, use a cleaning agent to assist in cleaning during this process, place the substrate in an ultrasonic cleaning machine after cleaning, and then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence. After the ultrasonic cleaning is completed, the substrate is transferred to a dust-free shed to remove residual liquid on the surface;

[0056] Among them, the cleaning time is 10 minutes, and the ultrasonic cleaning time is 30 minutes;

[0057] The residual liquid is removed by blowing away the residual liquid on the surface of the substrate with high-pressure pure nitrogen gas;

[0058] Step 2, preparing an electron transport layer on the pretreated substrate;

[0059] The substrate obtained after pretreatment was transferred to a rotary evaporator and evaporated 30 nm thick C60 as an electron transport layer;

[0060] Among them, the evaporation time is 30min;

[0061] Step 3, preparing a perovskite layer based on step 2;

[0062] 0.8 mmol of inorganic perovskite powder was dissolved in a mixed solvent of 0.1 mL of dimethylformamide (DMF) and 0.8 mL of dimethyl sulfoxide (DMSO) to obtain a perovskite precursor solution;

[0063] Then, the perovskite precursor solution was spin-coated on the surface of the electron transport layer obtained in step 2, the spin-coating speed was 5000 rpm, the spin-coating time was 60 seconds, and 0.6 mL of ethyl acetate was added to the rotating surface as an anti-solvent before the spin-coating was completed; finally, pre-crystallization was performed at 45° C. for 2 minutes, and then annealing was performed at 200° C. for 12 minutes to obtain a perovskite photoactive layer with a thickness of 250 to 350 nm;

[0064] Step 4: prepare a hole transport layer based on step 3; dissolve 50 mg of Spiro-OMeTAD in 1 mL of chlorobenzene solution, mix well to obtain a Spiro-OMeTAD spin coating solution, take 80 μL of Spiro-OMeTAD spin coating solution and deposit it on the surface obtained in step 3, the spin coating speed is 4000 rpm, and the spin coating time is 30 s;

[0065] Step 5, preparing an electrode on the surface of the substrate obtained in step 4 to complete the preparation of the perovskite solar cell;

[0066] The electrode is prepared by evaporating a 50-80 nm thick Au electrode on the surface of the Spiro-OMeTAD hole transport layer obtained in step 4 under a vacuum degree of 3×10-4 to 6×10-4 Pa.

[0067] The ZnO-based perovskite solar cell of the present invention can be applied to photovoltaic solar cells, or to solar street lamps and other devices that can be used for photovoltaic power generation.

[0068] The ZnO-based perovskite solar cell produced by the above steps, the perovskite powder can solve the problems of stoichiometric ratio deviation and the introduction of non-perovskite impurities, improve the crystallization quality of the perovskite film, thereby realizing efficient, stable and repeatable inorganic perovskite solar cell devices. At the same time, it is produced by spin coating, which is convenient for large-scale production and ensures the uniformity of the hole transport layer and the perovskite layer. The electron transport layer is produced by evaporation, so that the photoelectric conversion rate of the ZnO-based perovskite solar cell is higher.

[0069] Embodiment three:

[0070] A method for preparing a ZnO-based perovskite solar cell comprises the following steps:

[0071] Step 1, selecting a substrate and pre-treating the substrate;

[0072] The pretreatment method is to first rinse the substrate with deionized water, use a cleaning agent to assist in cleaning during this process, place the substrate in an ultrasonic cleaning machine after cleaning, and then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence. After the ultrasonic cleaning is completed, the substrate is transferred to a dust-free shed to remove residual liquid on the surface;

[0073] Among them, the cleaning time is 10 minutes, and the ultrasonic cleaning time is 30 minutes;

[0074] The residual liquid is removed by blowing away the residual liquid on the surface of the substrate with high-pressure pure nitrogen gas;

[0075] Step 2, preparing an electron transport layer on the pretreated substrate;

[0076] The substrate obtained after pretreatment was transferred to a rotary evaporator and evaporated 30 nm thick C60 as an electron transport layer;

[0077] Among them, the evaporation time is 30min;

[0078] Step 3, preparing a perovskite layer based on step 2;

[0079] 1 mmol of inorganic perovskite powder was dissolved in a mixed solvent of 0.15 mL of dimethylformamide (DMF) and 1 mL of dimethyl sulfoxide (DMSO) to obtain a perovskite precursor solution;

[0080] Then the perovskite precursor solution was spin-coated on the surface of the electron transport layer obtained in step 2, the spin-coating speed was 4500 rpm, the spin-coating time was 55 seconds, and 0.3 mL of ethyl acetate was added to the rotating surface as an anti-solvent before the spin-coating was completed; finally, pre-crystallization was performed at 50° C. for 1.5 minutes, and then annealing was performed at 180° C. for 10 minutes to obtain a perovskite photoactive layer with a thickness of 250 to 350 nm;

[0081] Step 4: prepare a hole transport layer based on step 3; dissolve 61 mg of Spiro-OMeTAD in 1 mL of chlorobenzene solution, mix well to obtain a Spiro-OMeTAD spin coating solution, take 80 μL of Spiro-OMeTAD spin coating solution and deposit it on the surface obtained in step 3, the spin coating speed is 4000 rpm, and the spin coating time is 30 s;

[0082] Step 5, preparing an electrode on the surface of the substrate obtained in step 4 to complete the preparation of the perovskite solar cell;

[0083] The electrode is prepared by evaporating a 50-80 nm thick Au electrode on the surface of the Spiro-OMeTAD hole transport layer obtained in step 4 under a vacuum degree of 3×10-4 to 6×10-4 Pa.

[0084] The ZnO-based perovskite solar cell of the present invention can be applied to photovoltaic solar cells, or to solar street lamps and other devices that can be used for photovoltaic power generation.

[0085] The ZnO-based perovskite solar cell produced by the above steps, the perovskite powder can solve the problems of stoichiometric ratio deviation and the introduction of non-perovskite impurities, improve the crystallization quality of the perovskite film, thereby realizing efficient, stable and repeatable inorganic perovskite solar cell devices. At the same time, it is produced by spin coating, which is convenient for large-scale production and ensures the uniformity of the hole transport layer and the perovskite layer. The electron transport layer is produced by evaporation, so that the photoelectric conversion rate of the ZnO-based perovskite solar cell is higher.

[0086] Embodiment 4:

[0087] A method for preparing a ZnO-based perovskite solar cell comprises the following steps:

[0088] Step 1, selecting a substrate and pre-treating the substrate;

[0089] The pretreatment method is to first rinse the substrate with deionized water, use a cleaning agent to assist in cleaning during this process, place the substrate in an ultrasonic cleaning machine after cleaning, and then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence. After the ultrasonic cleaning is completed, the substrate is transferred to a dust-free shed to remove residual liquid on the surface;

[0090] Among them, the cleaning time is 20 minutes, and the ultrasonic cleaning time is 30 minutes;

[0091] The residual liquid is removed by blowing away the residual liquid on the surface of the substrate with high-pressure pure nitrogen gas;

[0092] Step 2, preparing an electron transport layer on the pretreated substrate;

[0093] The substrate obtained after pretreatment was transferred to a rotary evaporator and evaporated 30 nm thick C60 as an electron transport layer;

[0094] Among them, the evaporation time is 30min;

[0095] Step 3, preparing a perovskite layer based on step 2;

[0096] 0.8 mmol of inorganic perovskite powder was dissolved in a mixed solvent of 0.2 mL of dimethylformamide (DMF) and 1 mL of dimethyl sulfoxide (DMSO) to obtain a perovskite precursor solution;

[0097] Then, the perovskite precursor solution was spin-coated on the surface of the electron transport layer obtained in step 2, the spin-coating speed was 4000 rpm, the spin-coating time was 50 seconds, and 0.4 mL of ethyl acetate was added to the rotating surface as an anti-solvent before the spin-coating was completed; finally, pre-crystallization was performed at 45°C for 2 minutes, and then annealing was performed at 200°C for 10 minutes to obtain a perovskite photoactive layer with a thickness of 250 to 350 nm;

[0098] Step 4: prepare a hole transport layer based on step 3; dissolve 55 mg of Spiro-OMeTAD in 1 mL of chlorobenzene solution, mix well to obtain a Spiro-OMeTAD spin coating solution, take 80 μL of Spiro-OMeTAD spin coating solution and deposit it on the surface obtained in step 3, the spin coating speed is 4000 rpm, and the spin coating time is 30 s;

[0099] Step 5, preparing an electrode on the surface of the substrate obtained in step 4 to complete the preparation of the perovskite solar cell;

[0100] The electrode is prepared by evaporating a 50-80 nm thick Au electrode on the surface of the Spiro-OMeTAD hole transport layer obtained in step 4 under a vacuum degree of 3×10-4 to 6×10-4 Pa.

[0101] The ZnO-based perovskite solar cell of the present invention can be applied to photovoltaic solar cells, or to solar street lamps and other devices that can be used for photovoltaic power generation.

[0102] The ZnO-based perovskite solar cell produced by the above steps, the perovskite powder can solve the problems of stoichiometric ratio deviation and the introduction of non-perovskite impurities, improve the crystallization quality of the perovskite film, thereby realizing efficient, stable and repeatable inorganic perovskite solar cell devices. At the same time, it is produced by spin coating, which is convenient for large-scale production and ensures the uniformity of the hole transport layer and the perovskite layer. The electron transport layer is produced by evaporation, so that the photoelectric conversion rate of the ZnO-based perovskite solar cell is higher.

[0103] Embodiment five:

[0104] A method for preparing a ZnO-based perovskite solar cell comprises the following steps:

[0105] Step 1, selecting a substrate and pre-treating the substrate;

[0106] The pretreatment method is to first rinse the substrate with deionized water, use a cleaning agent to assist in cleaning during this process, place the substrate in an ultrasonic cleaning machine after cleaning, and then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence. After the ultrasonic cleaning is completed, the substrate is transferred to a dust-free shed to remove residual liquid on the surface;

[0107] Among them, the cleaning time is 25 minutes, and the ultrasonic cleaning time is 30 minutes;

[0108] The residual liquid is removed by blowing away the residual liquid on the surface of the substrate with high-pressure pure nitrogen gas;

[0109] Step 2, preparing an electron transport layer on the pretreated substrate;

[0110] The substrate obtained after pretreatment was transferred to a rotary evaporator and evaporated 30 nm thick C60 as an electron transport layer;

[0111] Among them, the evaporation time is 30min;

[0112] Step 3, preparing a perovskite layer based on step 2;

[0113] 1.1 mmol of inorganic perovskite powder was dissolved in a mixed solvent of 0.2 mL of dimethylformamide (DMF) and 0.9 mL of dimethyl sulfoxide (DMSO) to obtain a perovskite precursor solution;

[0114] Then, the perovskite precursor solution was spin-coated on the surface of the electron transport layer obtained in step 2, the spin-coating speed was 4800 rpm, the spin-coating time was 57 seconds, and 0.5 mL of ethyl acetate was added to the rotating surface as an anti-solvent before the spin-coating was completed; finally, pre-crystallization was performed at 53° C. for 2 minutes, and then annealing was performed at 190° C. for 10 minutes to obtain a perovskite photoactive layer with a thickness of 250 to 350 nm;

[0115] Step 4: prepare a hole transport layer based on step 3; dissolve 65 mg of Spiro-OMeTAD in 1 mL of chlorobenzene solution, mix well to obtain a Spiro-OMeTAD spin coating solution, take 80 μL of Spiro-OMeTAD spin coating solution and deposit it on the surface obtained in step 3, the spin coating speed is 4000 rpm, and the spin coating time is 30 s;

[0116] Step 5, preparing an electrode on the surface of the substrate obtained in step 4 to complete the preparation of the perovskite solar cell;

[0117] The electrode is prepared by evaporating a 50-80 nm thick Au electrode on the surface of the Spiro-OMeTAD hole transport layer obtained in step 4 under a vacuum degree of 3×10-4 to 6×10-4 Pa.

[0118] The ZnO-based perovskite solar cell of the present invention can be applied to photovoltaic solar cells, or to solar street lamps and other devices that can be used for photovoltaic power generation.

[0119] The ZnO-based perovskite solar cell produced by the above steps, the perovskite powder can solve the problems of stoichiometric ratio deviation and the introduction of non-perovskite impurities, improve the crystallization quality of the perovskite film, thereby realizing efficient, stable and repeatable inorganic perovskite solar cell devices. At the same time, it is produced by spin coating, which is convenient for large-scale production and ensures the uniformity of the hole transport layer and the perovskite layer. The electron transport layer is produced by evaporation, so that the photoelectric conversion rate of the ZnO-based perovskite solar cell is higher.

[0120] The experimental object is a 500W xenon lamp with an AM1.5G filter as the light source, and the experimental environment is 100mw / cm 2 Under the irradiation of light intensity, the performance of the above perovskite solar cell is measured;

[0121] Among them, the effective light receiving area of ​​the battery is 0.04cm';

[0122] Among them, the performance parameters such as open circuit voltage (V.), fill factor (FF) and conversion efficiency (PCE) are as follows;

[0123] The following table shows the performance parameters of the ZnO-based perovskite solar cells after being treated with different polymers:

[0124] Serial number Voc(v) <![CDATA[Js(mA\cm 2 )]]> FF(%) PCE(%) Experiment 1 1.21 24 75.4 22.7 Experiment 2 1.21 24.1 75 23.8 Experiment 3 1.20 25.4 77.9 21.6 Experiment 4 1.15 23 76.8 22.4 Experiment 5 1.15 22.5 75.9 23.6

[0125] As can be seen from the above table, the open circuit voltage, circuit current, fill factor and photoelectric conversion efficiency of ZnO-based perovskite solar cells composed of various polymers are significantly improved. They have a good water vapor isolation effect, preventing water vapor from damaging the perovskite layer, thereby increasing the service life of the battery.

[0126] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A ZnO-based perovskite solar cell, characterized in that: It includes a substrate, an electron transport layer, a perovskite layer, a hole transport layer, and an electrode; The substrate includes one of soda-lime glass, stainless steel foil, titanium foil, PET, and FTO conductive glass; The electron transport layer is made of C60 material, and the perovskite layer is made of inorganic perovskite powder with an amount of 0.8 to 1.2 mmol; The hole transport layer is Spiro-OMeTAD 50-72 mg, and the electrode is a vapor-deposited Au electrode.

2. A method for preparing a ZnO-based perovskite solar cell, comprising the following steps: Step 1, selecting a substrate and pre-treating the substrate; The pretreatment method is to first rinse the substrate with deionized water, use a cleaning agent to assist in cleaning during this process, place the substrate in an ultrasonic cleaning machine after cleaning, and then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence. After the ultrasonic cleaning is completed, the substrate is transferred to a dust-free shed to remove residual liquid on the surface; Step 2, preparing an electron transport layer on the pretreated substrate; The substrate obtained after pretreatment was transferred to a rotary evaporator and evaporated 30 nm thick C60 as an electron transport layer; Step 3, preparing a perovskite layer based on step 2; Dissolving 0.8-1.2 mmol of inorganic perovskite powder in a mixed solvent of 0.1-0.2 mL of dimethylformamide (DMF) and 0.8-1.0 mL of dimethyl sulfoxide (DMSO) to obtain a perovskite precursor solution; Then, the perovskite precursor solution is spin-coated on the surface of the electron transport layer obtained in step 2, the spin-coating speed is 3000-5000 rpm, the spin-coating time is 40-60 seconds, and 0.1-0.6 mL of ethyl acetate is added to the rotating surface as an anti-solvent before the spin-coating is completed, and finally, pre-crystallization is performed at 45-55° C., and then annealing is performed at 160-200° C. to obtain a perovskite photoactive layer with a thickness of 250-350 nm; Step 4: prepare a hole transport layer based on step 3; dissolve 50-72 mg Spiro-OMeTAD in 0.8-1 mL chlorobenzene solution, mix well to obtain a Spiro-OMeTAD spin coating solution, and deposit 80 μL Spiro-OMeTAD spin coating solution on the surface obtained in step 3; Step 5, preparing an electrode on the surface of the substrate obtained in step 4 to complete the preparation of the perovskite solar cell; The electrode is prepared by evaporating a 50-80 nm thick Au electrode on the surface of the Spiro-OMeTAD hole transport layer obtained in step 4 under a vacuum degree of 3×10-4 to 6×10-4 Pa.

3. The method for preparing a ZnO-based perovskite solar cell according to claim 2, characterized in that: The cleaning time in step 1 is greater than 10 minutes, and the ultrasonic cleaning time is 30 minutes.

4. The method for preparing a ZnO-based perovskite solar cell according to claim 2, characterized in that: The residual liquid removal method in step 1 is to blow away the residual liquid on the surface of the substrate with high-pressure pure nitrogen gas.

5. The method for preparing a ZnO-based perovskite solar cell according to claim 2, characterized in that: The evaporation time in step 2 is 10-30 minutes.

6. The method for preparing a ZnO-based perovskite solar cell according to claim 2, characterized in that: The pre-crystallization time in step 3 is 1-2 minutes, and the annealing time is 8-12 minutes.

7. The method for preparing a ZnO-based perovskite solar cell according to claim 2, characterized in that: The spin coating speed in step 4 is 4000 rpm, and the spin coating time is 30 s.

8. The use of a ZnO-based perovskite solar cell according to claim 1, characterized in that: The ZnO-based perovskite solar cell of the present invention can be applied to photovoltaic solar cells, or to solar street lamps and other devices that can be used for photovoltaic power generation.